The Isolatıon, Characterızatıon, and Antıfungal Assay of Lactıc Acıd Bacterıa Isolated from Green Glutınous Rıce Tape Agaınst Aspergillus flavus - Nasution, Musyirna Rahmah; Aulya, Nurliza; Dona, Rahma; Ningsih, Yozi Fiedya (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2025)
Green glutinous rice tape is a fermented food made from glutinous rice, katuk leaves (Sauropus androgynus), and yeast, originating from Tembilahan, Riau Province. This product can serve as a source of lactic acid bacteria (LAB) capable of producing antimicrobial compounds to inhibit pathogenic microorganisms, including Aspergillus flavus, a well-known spoilage fungus in food products. However, to date, no reports have explored the ability of LAB from green glutinous rice tape to inhibit the growth of Aspergillus flavus. This study aimed to isolate LAB from green glutinous rice tape, conduct macroscopic, microscopic, and biochemical characterizations, and evaluate the antifungal activity of the LAB isolates against Aspergillus flavus using the good diffusion method. The isolation process yielded four LAB isolates from Tembilahan green tape (TKHT-2, TKHT-3, TKHT-5, and TKHT-7), which were identified as members of the genus Lactobacillus sp., with antifungal activities of 25.50 ± 5.78 mm, 24.33 ± 0.62 mm, 22.16 ± 6.56 mm, and 18.66 ± 4.28 mm, respectively. The corresponding cell-free supernatants (CFS) from these isolates (TKHT-S2, TKHT-S3, TKHT-S5, and TKHT-S7) also demonstrated antifungal activity with inhibition zones of 19.83 ± 3.47 mm, 19.83 ± 4.24 mm, and 14.50 ± 3.26 mm, respectively. LAB cells and their cell-free supernatants partially inhibited Aspergillus flavus, indicating a fungistatic effect. These findings suggest the potential application of LAB from green glutinous rice tape as a natural preservative or antifungal agent in food products.